Minimally invasive technique for suprasyndesmotic ankle fracture fixation: clinical and radiographic analysis - Hobi, Renê; Galera, Rodolfo; Campos Filho, José; Mugnol, Leonardo (Journal of the Foot & Ankle, 2020)
Objective: To evaluate the clinical and radiographic results of suprasyndesmotic ankle fracture fixation with a minimally invasive technique. Methods: Retrospective study of 11 patients with suprasyndesmotic fractures of the lateral malleolus who underwent surgery between 2016 and 2018. Retrospective analysis of medical records considered the following: radiographic assessments (preoperative, immediate postoperative, six weeks postoperative), clinical evaluation, and strength scale and movement test results. Results: Of the 18 patients qualified for inclusion, 7 failed to appear at the follow-up appointment and were excluded. The patients’ age varied from 20 to 53 years, and 72.7% were male. The trauma mechanisms included torsion (46% of the cases), automobile accidents (36.4%) and direct trauma (17.6%). The mean time between trauma and definitive surgery was 3.27 days. The mean talocrural angle in the preoperative period was 83.13º, ranging from 80.63º in the immediate postoperative period to 81.27º at 6 months postoperatively. Approximately 90% of the patients did not lose strength. Regarding the range of motion, the mean dorsiflexion and plantar flexion 6 months postoperatively were 10.72º and 34.4º, respectively. Conclusion: The minimally invasive technique had excellent technical results in patients treated surgically for ankle fractures and required smaller incisions than conventional surgery. Osteolysis or fatigue of the osteosynthesis material is a possibility with this technique, which generally occurred between three and four months postoperatively. Level of Evidence IV; Therapeutic Studies; Case series.